Comparative whole-building life cycle assessment of renovation and new construction. (15th August 2019) - Hasik, Vaclav; Escott, Elizabeth; Bates, Roderick; Carlisle, Stephanie; Faircloth, Billie; Bilec, Melissa M.
Abstract: Renovation of existing buildings has been identified as a major strategy for reducing the environmental impacts associated with building construction. From the perspective of embodied impacts, repurposing existing structures can reduce the amount of new materials that have to be extracted, manufactured, and installed. While the literature on energy efficiency retrofitting is relatively abundant, a smaller number of studies investigate the differences in whole-building embodied impacts of major renovations. This study presents an approach for conducting a whole-building life cycle assessment (LCA) on building renovation projects, suggests an approach for conducting comparative assessments between renovation and new construction, and demonstrates the approach on an adaptive reuse case study. The approach consists of comparing the full life cycle impacts of the existing building to the sum of the life cycle impacts of the components added in the renovation and the maintenance and replacement needs of the existing/reused components. The case study showed 53–75% reductions across 6 different environmental impact categories when the renovation was compared to a new construction scenario. The reuse of the structural and envelope components provided the majority of the reductions, as most of the renovation was of the interior components and finishes. The presented work can be used as a model for consistent LCAs on other renovation projects and to show designers, policy makers, and building owners the environmental benefits of adaptive reuse over new construction as a result of reduced need for new building materials. Highlights: Clarified terminology for use in life cycle assessment (LCA) of renovations. Proposed scope for renovation LCA that is comparable to new construction LCA. Adaptive reuse case study showed 53-75% reduction in major environmental impacts. Majority of the case study renovation impacts were due to non-structural components.